STUDI PENDAPATAN NELAYAN TRADISIONAL DI PESISIR PANTAI KABUPATEN TAKALAR - Amir, Amir; Romadhoni, Buyung; Rasulong, Ismail; Akhmad, Akhmad; Ali, Muhammad Yunus (Patria Artha Journal of Accounting dan Financial Reporting, 2020)
Traditional fishermen are characterized as poor people with low quality of food and housing, low savings and investment and low standards of living. The income of fishermen's fishing business is very different from that of traders and farmers. If traders can calculate their profit every month, as well as farmers can predict their yields, this is not the case with fishermen whose activities are full of uncertainty and are speculative and volatile. When compared to farmers, fishermen's non-fishing income is less varied because farmers have more time to work outside of agriculture. This study aims to determine the amount of income of traditional fishermen in the Coastal Coast of Takalar Regency. This research was conducted in the Coastal Coast of Takalar Regency. The population in this study were all fishermen who use outboard motor fleets in fishing business on the coast of Takalar Regency. Sampling was done by random sampling method and selected 58 fishermen respondents who are considered to represent all populations. The data obtained were then analyzed using descriptive analysis and Break Event Points. The results showed that the average amount of profit obtained by fishermen in one fishing trip was Rp. 288,900. Meanwhile, the results of the break even point analysis show that the fishermen are at the main point of return when they catch 11.11 kg of fish caught for one time fishing.